2022
DOI: 10.30621/jbachs.959016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Covid-19 Triage Assessment Scale in Patients Attending the Emergency Department

Abstract: Objective: To predict SARS-CoV-2 PCR positivity on the basis of symptoms and contact history of individuals who attend emergency department Methods: The data for the study which was of a prospective-methodological type were collected from 503 patients who attended emergency department of a hospital with suspected Covid-19 between 02 January - 15 March 2021 and were given Polymerase chain reaction (PCR) test. Covid 19 Visual Triage Scale (VTS) and questionnaire were used for collecting data. Distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The Thanatophobia Scale mean score of nurses was moderate at 31.74 ± 10.08 in this study. There have been studies in our country examining the thanatophobia levels of nurses and reported moderate to high levels [11,[20][21][22]. In a qualitative study by De Swardt and Fouche (2017), it was determined that nurses who gave post-mortem care to the deceased in the intensive care unit experienced thanatophobia by confronting the reality of their own death [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Thanatophobia Scale mean score of nurses was moderate at 31.74 ± 10.08 in this study. There have been studies in our country examining the thanatophobia levels of nurses and reported moderate to high levels [11,[20][21][22]. In a qualitative study by De Swardt and Fouche (2017), it was determined that nurses who gave post-mortem care to the deceased in the intensive care unit experienced thanatophobia by confronting the reality of their own death [23].…”
Section: Discussionmentioning
confidence: 99%
“…The scale was developed by Friborg et al and was translated into Turkish and veri ed for validity and reliability by Basim and Çetin [18,19]. It contains 33 items and 5 subdimensions, which are 'structural style' (3,9,15,21), 'perception of future' (2,8,14,20), 'family coherence' (5,11,17,23,26,32), 'perception of self' (1,7,13,19,28,31), 'social competence' (4,10,16,22,25,29) and 'social resources' (6, 12,18,24,27,30,33). If increased scores are to indicate increased resilience, the answer boxes should be rated from 1 to 5 from left to right.…”
Section: Psychological Resilience Scale For Adults-prsamentioning
confidence: 99%